(untitled) (Research, Society and Development, 2021)
In the mechanized harvesting system of sugar cane, a considerable amount of plant residues, called straw or straw (dry leaves, sheaths, pointers and stems), is accumulated in the soil. The accumulation of this straw causes physical and biological changes in the soil, improving soil fertility under these conditions. The inadequate management of agroecosystems leads to the degradation of the edaphic environment and, consequently, to the detriment of its functionality within biological systems. The impacts that occur on the soil due to changes in management must be evaluated. For this purpose, the edaphic fauna becomes an excellent bioindicator, due to its close relationship with the processes that come from the litter-soil compartment and its peculiar susceptibility to interference in the soil. environment, the composition of the edaphic fauna community reflects the functionality of the ecosystem and, together with the density, can explain the changes resulting from anthropic interference in the vegetation cover. Vegetable coverings and different cultivation systems act directly on the population of the edaphic fauna, reducing the density and diversity of communities in relation to a natural ecosystem. Through the study of edaphic fauna, in addition to assessing soil quality, having a greater understanding of the production system that this soil supports, since it is closely linked to the processes of nutrient cycling and decomposition of organic matter at the interface soil-plant.